Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd003850.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic systemic antifungal agents to prevent mortality and morbidity in very low birth weight infants

Abstract: Prophylactic systemic antifungal therapy reduces the incidence of invasive fungal infection in very low birth weight infants. This finding should be interpreted cautiously. The incidence of invasive fungal infection was very high in the control groups of some of the included trials. Furthermore, the trials may have been affected by ascertainment bias since use of prophylactic fluconazole may reduce the sensitivity of microbiological culture for detecting fungi in blood, urine, or cerebrospinal fluid. Meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…From the aforementioned data, there is overwhelming evidence in support of fluconazole prophylaxis and the data are consistent with the recent Cochrane review [46]. The Cochrane review data revealed a statistically significant reduction in invasive fungal infections in infants who received prophylaxis (typical relative risk: 0.23; 95% CI: 0.11-0.46), with a number needed to treat of nine (95% CI: 6-17) [46].…”
Section: Fluconazole or Nystatin?supporting
confidence: 70%
“…From the aforementioned data, there is overwhelming evidence in support of fluconazole prophylaxis and the data are consistent with the recent Cochrane review [46]. The Cochrane review data revealed a statistically significant reduction in invasive fungal infections in infants who received prophylaxis (typical relative risk: 0.23; 95% CI: 0.11-0.46), with a number needed to treat of nine (95% CI: 6-17) [46].…”
Section: Fluconazole or Nystatin?supporting
confidence: 70%
“…To date there have been five randomized controlled trials (RCTs) [52,[65][66][67][68], eight retrospective reviews [19,20,[73][74][75][76][77][78], and a Cochrane review [79] examining fluconazole prophylaxis in neonates.…”
Section: Neonatal Clinical Studiesmentioning
confidence: 99%
“…A reduction in invasive candidiasis with FP has been previously demonstrated in multiple randomized controlled trials and retrospective cohort studies. [5][6][7][8]13 Limited studies using a more targeted approach of prophylaxis to select high risk groups have reported success. Uko et al 14 reported the efficacy of targeted short-term prophylaxis during discrete periods of antibiotic administration in reducing invasive fungal infection, in comparison with a historic control who did not receive any prophylaxis.…”
Section: Targeted Fluconazole Prophylaxis In Preterm Infantsmentioning
confidence: 99%
“…3 Several studies have demonstrated that prophylactic fluconazole decreases fungal colonization and subsequent invasive fungal infection in PT infants. [4][5][6][7][8] The duration of prophylaxis in most of these studies is from 4 to 6 weeks, starting at birth to 3 days of age. 4,5,8 The risk of invasive candidiasis persists from birth to 3 months, with the highest risk reported to be between 11 and 20 days of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation